The aglycone diosmetin has the higher perpetrator drug-drug interaction potential compared to the parent flavone diosmin - Bajraktari-Sylejmani, Gzona; Weiß, Johanna (Journal of functional foods, 2020)
The flavone diosmin is part of everyday nutrition but also marketed as medicine or nutritional supplement against various diseases. Although the manufacturers declare safe administration, several data indicate inhibition of drug metabolising enzymes or drug transporters by diosmin and its aglycone diosmetin leading to interactions with drugs. Our study intended to add missing data to the interaction profile of both flavones. Diosmetin revealed to be the compound with the higher interaction potential in vitro. It potently inhibited breast cancer resistance protein, several organic anion transporting polypeptides, cytochrome P450 1A2, 2C19, and 3A4 in the lower micromolar range, whereas diosmin did either not inhibit these proteins or was less potent. Both compounds induced P-glycoprotein expression and activated the pregnane X and the aryl hydrocarbon receptor. Thus, diosmetin might act as a perpetrator in drug-drug interactions. However, so far, clinical data on relevant interactions with clinically applied drugs is rare.
Gesehen am 20.05.2020